Utilizing Comparative Method for Analyzing the Course of Basic Design on Vorlehre and Three-Dimensional Form - Lucius, C R; Santosa, I; Nugraha, A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The comparative method is a research strategy oriented to case study comparisons, where the analysis of each case study becomes a combination of the characteristics of the phenomena to be defined. Its case study analysis is interpretive of historical evidence, with the aim of explaining comparable processes for generating generalizations about the causes of the phenomenon. This comparative method is applied in building a logical foundation to identify the similarities and differences of the Course of Basic Design which was carried out at the Vorlehre of the Staatliches Bauhaus and the Three-Dimensional Form of Institut Teknologi Bandung. The comparison is focused on the definition of the comparable objects based on the interpretation of the available literature data. This analysis can explain a comparison pattern, which will be used to compare Bauhaus design work and Indonesian design work. The results of this study are part of a study on the influence of Bauhaus on design in Indonesia.